The effect of self-learning module on nursing students' clinical competency: A pilot study - Shahin Tohidi; Hossein KarimiMoonaghi; Arezoo Shayan; Hassan Ahmadinia (Wolters Kluwer Medknow Publications, 2019)
Background: Self-learning module (SLM) is designed for independent learning. In this study, the hypothesis that SLM is effective to some extent in improving clinical competence in nursing students was tested. Materials and Methods: The study employed a randomized controlled design. In this study, 46 nursing students were randomized into the control or intervention group. Study tools included a demographic information form and nursing skills checklist. Unlike the control group, the intervention group received clinical SLM. Nursing students' clinical competency was measured at the end of the intervention through objective structured clinical examination. Statistical analysis was performed in SPSS software. A p value < 0.050 was considered statistically significant. Results: In total, 46 students participated in this study. The Mean (SD) age of the study participants was 18.80 (1.06) years. There was a significant difference in students' clinical competency between the control and intervention groups (Mann-Whitney U-test:p= 0.010). Mean (SD) of clinical competency in the control and SLM groups was 58.19 (6.41) and 62.83 (6.05), respectively. Results of the group equivalency test indicated that all demographic variables were equivalent between the groups. Moreover, there was no significant difference between women and men in terms of clinical competency. Conclusions: According to the results, the use of SLM could help the students enhance the quality of nursing clinical competency.